ANALISIS REAKSI PASAR ATAS PENGUMUMUMAN ANNUAL REPORT AWARD TAHUN 2014-2016 - Biggy Biggy; Robert Jao (Jurnal Bisnis dan Kewirausahaan, 2019)
This study aims to determine the difference in abnormal returns and trading frequency of the winners of Annual Report Award before and after the awards was announced. This study uses the event study period of 3 days before the announcement and 3 days after the announcement.The sample is companies listed on the Indonesia Stock Exchange (IDX) and won the Annual Report Award (ARA) in 2014-2016. The samples are selected by using purposive sampling method and obtained 33 samples. Method of data analysis using paired sample t-test. Test result showed that the publication of the Annual Report Award (ARA) in 2014-2016 wasn’t responded by the market no significant difference in abnormal returns and frequency before and after publication. This suggest that the publication of ARA 2014-2016 doesn’t have the information content that able to change the investor’s decision to invest.